Upaya Penyelesaian Tanah Absente di Desa Sumberjati Kecamatan Silo Kabupaten Jember - Encik Lukmanul Hakim (Fakultas Hukum Universitas Islam Jember, 2016)
Efforts Jember District Land Office in the completion of absentee land by way of absentee land owners who are resident and domiciled in Surabaya recommended moving to the village Sumberjati Silo Subdistrict Jember for land he owned in the village Sumberjati Silo Subdistrict Jember. The procedures performed by the owner of absentee land are to be resettled to the village Sumberjati, District Silo, Jember, namely to have an ID card, and in addition to avoid the process of land ownership absentee besides have an ID card, then the person who moved it should be completely move and settle down and carry out social activities in the daily keidupan Sumberjati village Silo Subdistrict Jember. In the resolution of absentee land in Jember District Land Office has a trick that can be used, namely the completion of actively and passively. Then Giving compensation to former owners of absentee land can be made directly and indirectly. Direct payments are compensation of absentee land owners of the recipients of land through the chairman of the Committee restribusi Lndreform district paid the former owner of the land.